2010
DOI: 10.1038/jhg.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype associations and human eye color

Abstract: Although eye color is usually modeled as a simple, Mendelian trait, further research and observation has indicated that eye color does not follow the classical paths of inheritance. Eye color phenotypes demonstrate both epistasis and incomplete dominance. Although there are about 16 different genes responsible for eye color, it is mostly attributed to two adjacent genes on chromosome 15, hect domain and RCC1-like domain-containing protein 2 (HERC2) and ocular albinism (that is, oculocutaneous albinism II (OCA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…This may suggest a shared promoter or some unknown transcriptional mechanisms involving the GABRB3 exon 1–3 region that is critical for Oca2 gene expression. It has also been previously reported that an intron in HERC2 contains the promoter region for Oca2 , suggesting complex transcriptional regulation of Oca2 by its adjacent genes (White and Rabago-Smith, 2011). The GABRB3 promoter region is critical for transcriptional factor binding (Tanaka et al, 2012a) and splicing as previously demonstrated (Kirkness and Fraser, 1993).…”
Section: Discussionmentioning
confidence: 69%
“…This may suggest a shared promoter or some unknown transcriptional mechanisms involving the GABRB3 exon 1–3 region that is critical for Oca2 gene expression. It has also been previously reported that an intron in HERC2 contains the promoter region for Oca2 , suggesting complex transcriptional regulation of Oca2 by its adjacent genes (White and Rabago-Smith, 2011). The GABRB3 promoter region is critical for transcriptional factor binding (Tanaka et al, 2012a) and splicing as previously demonstrated (Kirkness and Fraser, 1993).…”
Section: Discussionmentioning
confidence: 69%
“…The haplotypes of this region were previously suggested to increase eye colour prediction [6,20,5]. It was suggested [12,21] that the OCA2 allele rs1800407 A decreased the pigmentation level in the eye when found in cis phase with the HERC2 allele rs12913832 A, whereas the OCA2 allele rs1800407 A found in Page 11 of 23 A c c e p t e d M a n u s c r i p t cis phase with the HERC2 allele rs12913832 G will display little effect on the eye colour because the transcription of OCA2 is reduced.…”
Section: The Predictive Properties Of the Irisplex Prediction Modelmentioning
confidence: 99%
“…HERC1 has been implicated in membrane trafficking and cell proliferation/growth through its interactions with the ARF, Rab, clathrin, M2-pyruvate kinase, and TSC2 proteins (20 -23). HERC2 is one of two major genes responsible for eye color in humans (24). Several radiation and ethylnitrosourea-induced mutations at the mouse Herc2 locus cause neuromuscular tremor, runting, juvenile lethality, and sperm defects (25)(26)(27).…”
mentioning
confidence: 99%